Which Treatment Should Be Chosen for Acute Arterial Mesenteric Ischemia? Surgery or Endovascular Intervention? - Uludağ, Server Sezgin; Yurdacan, Müge; Samancı, Cesur; Güreş, Nazım; Şanlı, Ahmet Necati; Zengin, Abdullah Kağan (Cerrahpaşa Medical Journal, 2021)
Objective: In this study, we aimed to compare the results of both open laparotomy and endovascular intervention in patients admitted to our clinic with the diagnosis of acute mesenteric ischemia. Methods: Twelve patients who were treated with the diagnosis of acute mesenteric ischemia in our clinic between 2014 and 2020 were included in the study. Demographic data, clinical and radiological findings, open laparotomy, and endovascular intervention data of the patients were recorded. Results: The mean age of patients who underwent endovascular intervention was 56, and the mean age of patients who underwent open laparotomy was 72.1. White blood cell, lactate, C-reactive protein, lactate dehydrogenase, and creatinine values were slightly higher in patients treated with open laparotomy than those treated with endovascular intervention. The time from symptom onset to intervention was 13.9 hours in the endovascular intervention group and 17.1 hours in the open laparotomy group. Of the 6 patients who underwent open laparotomy, only 2 patients underwent superior mesenteric artery embolectomy and the other 4 underwent embolectomy and bowel resection. One of the 12 patients who underwent open laparotomy died due to anastomotic leakage The survival rate of the patients was recorded as 91.6%. Conclusion: Endovascular intervention is one of the first-choice methods with its minimally invasive feature in cases where intestinal necrosis has not yet developed. Open laparotomy is necessary for making a decision for resection because intestinal vitality can be seen. Making the right decision based on the patient's clinical, laboratory, and radiological findings will reduce morbidity and mortality in the patient. Cite this article as: Uludağ SS, Yurdacan M, Samancı C, Güreş N, Şanlı AN, Zengin AK. Which treatment should be chose for acute arterial mesenteric ischemia? Surgery or endovascular intervention? Cerrahpaşa Med J. November 20, 2021. 46(1):12-16.